2022
DOI: 10.3390/ma15196769
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior and Microstructure Evolution of a Novel Al-Zn-Mg-Li-Cu Alloy

Abstract: Lightweight structural alloys have broad application prospects in aerospace, energy, and transportation fields, and it is crucial to understand the hot deformation behavior of novel alloys for subsequent applications. The deformation behavior and microstructure evolution of a new Al-Zn-Mg-Li-Cu alloy was studied by hot compression experiments at temperatures ranging from 300 °C to 420 °C and strain rates ranging from 0.01 s−1 to 10 s−1. The as-cast Al-Zn-Mg-Li-Cu alloy is composed of an α-Al phase, an Al2Cu ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…From a microscopic perspective, the elastic modulus reflects the magnitude of the bonding forces between the atoms of the material [22]. Under quasi‐static load condition, the strain rate is low and the activity of the atoms is high, resulting in a smaller bond between the atoms, that is, a smaller modulus of elasticity; conversely, under dynamic load condition, the strain rate is higher, the activity of the atoms is low, the bond between the atoms is greater and the modulus of elasticity is larger.…”
Section: Full‐scale Testmentioning
confidence: 99%
“…From a microscopic perspective, the elastic modulus reflects the magnitude of the bonding forces between the atoms of the material [22]. Under quasi‐static load condition, the strain rate is low and the activity of the atoms is high, resulting in a smaller bond between the atoms, that is, a smaller modulus of elasticity; conversely, under dynamic load condition, the strain rate is higher, the activity of the atoms is low, the bond between the atoms is greater and the modulus of elasticity is larger.…”
Section: Full‐scale Testmentioning
confidence: 99%
“…When deformed within 400 to 460 °C and 0.001 to 0.1 s −1 , the phenomenon of localization deformation was observed. Wu [ 22 ] explored the compression response and microstructure mechanism of a new Al-Zn-Mg-Cu alloy from 300 to 420 °C and 0.01 to 10 s −1 . The characterization results demonstrated that the grain size increases with increasing deformation temperatures; meanwhile, the fraction of DRX increases with increasing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature plastic deformation is often used to change the geometric shape and optimize the microstructure of 7××× series aluminum alloy materials. The thermal deformation parameters (such as strain, strain rate, and deformation temperature) during high-temperature plastic deformation can significantly affect the flow stress and microstructure evolution of the alloy [ 8 , 9 , 10 ]. Isothermal compression experiments are often used to investigate the thermal deformation behavior of metals by accurately controlling deformation temperature, strain rate, and deformation amount, and have been used widely in Al-Zn-Mg-Cu aluminum alloys [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%